Identification of Factors that Impact on Syariah Bank Asset Growth in West Java Province - Rina Destiana; Tri Neliana (Britain International for Academic Research (BIAR-Publisher), 2021)
The syariah banking industry in Indonesia is experiencing various growth in accordance with national economic growth. One indicator of the growth of syariah banks can be seen from the growth in assets. The phenomenon of decreasing asset growth that occurs in syariah banks encourages the need for further research. This study aims to determine and analyze the effect of the number of office networks, Non Performing Financing, Financing to Deposit Ratio, returns on third party funds and the BI rate on the growth of syariah bank assets in West Java Province. This study uses secondary data published by the Financial Services Authority and Bank Indonesia. The research period is January 2016 to December 2019. The data analysis method used in this study is multiple linear regression analysis, which previously tested the classical assumptions and then tested the hypothesis. The results showed that only the return on third party funds had an effect on asset growth, while the number of office networks, Non-Performing Financing, Financing to Deposit Ratio and BI rate had no effect on the growth of syariah bank assets in West Java Province.